(untitled) (Research, Society and Development, 2020)
The hookah is a new trend of young people between the ages of 20 and 30, always present at parties or on conversation wheels, using glycerinated tobacco for their smoke, also known as essence. Knowing the harms of tobacco, used as the main component of hookah, such as cancer and breathing problems, it can also contain other possible causes for diseases such as pathogenic microorganisms. Thus, despite the widespread popularization of this practice, there is still little research on it. Therefore, the objective of this work was to perform microbiological analysis of the components of the hookah in order to find bacteria of pathological origin or not. For this, the in vitro inoculation methodology was used in petri dish containing solidified agar. In case of bacterial growth, the microorganisms were isolated and subjected to identification by biochemical tests. E. coli, E. aerogenes, K. pneumoniae were found in the hookah pieces. Therefore good hygiene and other countermeasures are required for smokers to prevent infections.